Ethnicity and resource allocation management: Practical consideration - Ogu, Sokari (Journal of Commerce, Management, and Tourism Studies, 2023)
This paper analyses the theoretical issues underlying the problems of ethnicity and resource sharing, basing its discussion on recent continental developments (as in Sierra Leone, Liberia, Sudan, Rwanda and Nigeria). Arguing for ethnic identification and integration into national development matrix, it notes that smaller group domination by the larger ones (or the reverse) does not only trigger suspicion and governance tension but engender political independence agitation that could culminate in disintegration of nations (as found in the former Yugoslavia and Soviet Union). Why do we have ethnic conflicts in different parts of the world at a time there is tremendous growth in education and modernization? What accounts for intra-country civil disturbances? Why do countries disintegrate? What are the behavioural tendencies of the majority/minority ruling class and how acceptable are they to the other parties? How equitable is resource sharing in different counties and communities? How homogeneous is the world we live in today? The above questions capture the mood of the people in various countries where ethnic tension has overshadowed economic development, triggered civic disobedience, caused coup de’tat and engendered loss of lives and property. In both developed and developing countries, ethnicity has been a dividing line between people. All these are developmental issues that present a lot of implications for other countries including Nigeria where ethnicity has not only caused a civil war but has been an impediment to democratization. This paper is written to address them and offer some policy direction in the light of many democratic disruptions and the attendant confusions presently experience in the country and elsewhere.